(3GdEceGd aj PcQ ef dQhGjI aj eSfO GdEeGe CMeO ef GdQLGd Shi ef PcQ aj JgPjH GdceGds - (3TeS GdOjf GHi GdeMGSf eMeO Hf Ydj Hf GdMSf Hf MeRg GdMSjfj GdOeTbj GdeGdcjs; (3YHO GdQMef Hf YHO Gddg Hf CMeO GdNKYeqj GdSgjdqj,J (B581 (3g` s
(3ChdgG (B:s
(3hHYO aEfg deG bVi Gddg YR hLd di ai GNJUGQ cJGH JgPjH GdceGd ai CSeGA GdQLGd dTjNfG GdMGaX CHj GdMLGL GdeRi s
(3BNQgG (B:s
(3GfgG SeYJ GdfHi Ydjg GdSdGe hgh jUdi HdfGS hhLgg Edi GdHjJ QhGg YfgG GHh Gdedjd hGddg CYde s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B147s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B65 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B29 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs